Analysis of Chinese adult residents receiving healthy lifestyle advice from medical institutions - Huiyan SUN; Limin WANG; Chun LI; Xiao ZHANG; Zhenping ZHAO; Mei ZHANG (Zhongguo gonggong weisheng)
ObjectiveTo understand the status of Chinese adult residents receiving healthy lifestyle advice from medical institutions and to provide evidence for promoting healthy lifestyles in China. MethodsData were collected from 170 208 residents aged ≥ 18 years from 298 monitoring sites in 31 provinces (autonomous regions, municipalities) in the 2018 China Chronic Disease and Risk Factor Surveillance Project. The data included demographic characteristics and information on receiving advice on six healthy lifestyle advice from medical institutions: no smoking, salt reduction, adequate fruit and vegetable intake, fat reduction, adequate exercise, and healthy weight. The study analyzed the prevalence of receiving the advice. ResultsAmong Chinese adult residents, (35.8%) received advice on no smoking, (50.3%) on salt reduction, (53.9%) on adequate fruit and vegetable intake, (51.1%) on fat reduction, (53.0%) on adequate exercise, and (46.8%) on healthy weight. Significant differences (all P < 0.001) were observed in the prevalence of receiving the six healthy lifestyle advice among adults of different ages, hypertension status, diabetes status, and atherosclerotic cardiovascular disease (ASCVD) risk. Significant differences (all P < 0.05) were also found between genders regarding advice on no smoking, fat reduction, adequate exercise, and healthy weight. Significant differences (all P < 0.01) were observed among different education levels regarding advice on no smoking, adequate fruit and vegetable intake, fat reduction, adequate exercise, and healthy weight. Significant differences (all P < 0.05) were found among different annual per capita household income levels regarding advice on salt reduction, adequate fruit and vegetable intake, fat reduction, adequate exercise, and healthy weight. Significant differences (all P < 0.05) were also observed among different residential areas regarding advice on adequate fruit and vegetable intake, fat reduction, adequate exercise, and healthy weight. ConclusionThe proportions of Chinese adults receiving advice on no smoking, salt reduction, adequate fruit and vegetable intake, fat reduction, adequate exercise, and healthy weight from medical institutions were all relatively low, with the lowest proportion receiving advice on no smoking. Adults with lower education levels, lower income levels, and those residing in rural areas had lower proportions of receiving healthy lifestyle advice.